Assessment frequency in introductory computer programming disciplines. - Brito, Miguel A.; de Sá-Soares, Filipe (Computers in Human Behavior, 2014)
Highlights: [•] Weekly assessment as an effective way of leading students by the success path. [•] Weekly assessment demands automated assessment help. [•] Weekly assessment turned out to be perceived by students as an additional benefit.